LITERATURE REVIEW OF SOCIAL ECONOMIC LAW: POLICY, REGULATION AND SOCIAL IMPACT - Jackson Yumame; Loso Judijanto; Sapta Nur Fallah (CV. Adiba Aisha Amira, 2025)
Social economic law is a branch of law that governs policies and regulations that aim to address social inequalities and improve people's well-being. This often includes income redistribution policies, subsidies, and social welfare programmes designed to reduce poverty and inequality, while ensuring inclusive social and economic participation. Policy implementation faces challenges such as significant fiscal burdens and potential dependency of beneficiaries. Therefore, ongoing evaluation is required to ensure the policy is efficient and effective in achieving its social objectives. The results of this literature review provide important insights for better policy decision-making in the future.